ENGLISH AUDIOTEXTS SELECTION PROCEDURE FOR TEACHING LISTENING COMPREHENSION TO FUTURE INTERPRETERS - Olena Martynenko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article focuses on considering the audiotexts selection procedure for teaching future interpreters listening comprehension in English by correspondence. The author defines components of audiotexts selection criteria for teaching future interpreters by correspondence: primary (structural, lexical, phraseological, grammatical, functional authenticity, compliance with the students' English language level program requirements, and genre correspondence) and secondary (novelty and motivation criterion, open source Internet criterion, cultural authenticity, phonetic and acoustic peculiarities, and reaction authenticity criterion). Peculiarities of such genres of audiotexts as interview, announcements, news and lectures have been researched. Valid and invalid audiotexts for future interpreters have been analyzed. The examples of audiotexts correspondence/lack of correspondence to the defined criteria have been described.